The Potential Use of Avocado Leavers (Persea americana) as an Antidiabetict Agent - Kadek Abdi Saputra; Ni Nyoman Wahyu Udayani; I Putu Tangkas Suwantara (Gema Lingkungan Kesehatan, 2026)
Diabetes mellitus represents a chronic metabolic disorder that occurs when glycemic concentrations exceed normal levels. The use of natural ingredients such as avocado leaves (Persea americana) is an option due to the abundance of bioactive compounds that have antidiabetic potential. This article was written to present information and understanding related to the pharmacological activity of avocado leaves as an antidiabetic. It was compiled using a comparative review method based on data-driven literature searches. Based on the results of studies that have been conducted, it is known that avocado leaves have potential as an antidiabetic agent. In vivo studies show that avocado leaf extract can significantly lower blood sugar levels and regenerate the pancreas. In vitro studies reinforce the in vivo findings by showing high antioxidant activity (91.03%) and high α-amylase enzyme inhibition (88.95%), which is almost equivalent to acarbose. In addition, preliminary clinical studies show an improvement in glycemic levels in type 2 DM in humans that received avocado leaf decoction. Overall, avocado foliage extract shows great promising effects as an antidiabetic agent through various mechanisms, such as antioxidant activity, inhibition of glucose absorption enzymes, and regeneration of organs such as the pancreas and kidneys.